A 12-Month Randomized Clinical Trial of 38% SDF vs. Restorative Treatment. (April 2022) - Cleary, J.; Al-Hadidi, R.; Scully, A.; Yahn, W.; Zaid, Z.; Boynton, J.R.; Eckert, G.J.; Yanca, E.; Fontana, M.
Purpose: The aim of this 2-arm, parallel-group, 12-mo randomized clinical trial was to compare the effectiveness of semiannual application of 38% silver diamine fluoride (SDF) versus restorative treatment (RT) to manage cavitated caries lesions in primary teeth in a diverse population of children in Michigan. Methods: Children aged 2 to 10 y with at least 1 soft cavitated lesion (International Caries Detection and Assessment System 5 or 6) with no pain or signs/symptoms of irreversible pulpitis were recruited and randomly assigned to 2 intervention groups. One random lesion per child received 38% SDF (twice, at a 6-mo interval) or RT. All interventions and assessments were done by calibrated dentists. Primary outcome measures were clinical failure rates: minor (e.g., reversible pulpitis, active/soft lesion or progression, restoration loss or need for replacement/repair, secondary caries) and major (e.g., irreversible pulpitis, abscess, extraction). Parent, child, and provider acceptability was also assessed. Results: Ninety-eight children were enrolled and randomized, with a mean (SD) age of 4.8 y (1.8); 46% were female and their mean dmft + DMFT was 6.3 (3.9). Sixty-nine children were assessed at 12 mo (sample was within the planned 30% attrition rate). There were significantly more teeth with minor failures (SDF = 65%, RT = 23%, P ≤ 0.001) and major failures (SDF = 13%, RT = 3%, P ≤ 0.001) in the SDF group than the RT group; 74% of SDF-treated lesions were hard at 12 mo vs. 57% at 6 mo. Providers stated that SDF was easier, faster, and more preferable than RT ( P ≤ 0.001). No significant differences were found in parental satisfaction and acceptability. At 12 mo, children in the RT arm felt significantly ( P < 0.05) happier with their tooth appearance and stated that their visit to the dentist hurt less. Conclusion: At 12 mo, SDF-treated lesions had significantly more minor and major failures than RT, suggesting that SDF-treated teeth need to be closely monitored in a population at high caries risk (ClinicalTrials.gov NCT02601833). Knowledge of Transfer Statement: The results of this study can be used by clinicians when deciding whether to restore or apply silver diamine fluoride to cavitated lesions in primary teeth. Information on treatment outcomes and parent, child, and provider acceptability can help guide appropriate treatment decisions and need for monitoring.